How Children Learn Mathematics: A Guide for Parents and Teachers - Pamela Liebeck (Penguin UK)
Aimed at teachers and parents who are concerned with children from infancy through the primary years, this manual takes the reader through the development of abstract thought in children. It describes how children's experiences can be used to help them grasp the principles underlying such processes as addition, subtraction, multiplication, division and measurement. The author discusses fractions, decimals, calculators and computers, some theories of learning and problems of children who fail to understand mathematics.
Keywords: Professional Development Book, Math, PD Reading